Democratic Management at school: in search of participation and leadership - Cária, Neide Pena; Lambert-de-Andrade, Nelson (Revista Eletrônica de Educação, 2016)
Abstract The article is the result of studies performed in the Research Group in Education and Management (known as GPEG), certificated by the Vale do Sapucaí University and registered in the CNPq Directory. The study aims to expand the view about the so-called "democratic management" and the "participation" in the in the administration of school educational work. For this, are articulated theoretical and legal fundamentals to the challenges and issues that, normally, the managers face in the exercise of their function in daily school considering the contradictions and challenges, which they are exposed. Passing between the given power and the real power, the managers are pressed, on one hand, by the accountability and evaluation of results and, on the other, by the lack of autonomy and proper conditions for a democratic school management. Keywords: Education. Democratic Management. Participation. Gestão democrática na escola: em busca da participação e da liderança Resumo O artigo é fruto de estudos realizados no Grupo de Pesquisa em Educação e Gestão (GPEG), certificado pela Universidade do Vale do Sapucaí e registrado no Diretório do CNPq. O estudo objetiva ampliar o olhar para a denominada “gestão democrática” e a “participação” na administração do trabalho educativo da escola. Articula-se fundamentos teóricos e legais aos desafios e questões que, normalmente, os gestores enfrentam no exercício da sua função no cotidiano escolar em face de contradições e desafios a que estão expostos. Navegando entre o poder outorgado e o poder real, os gestores são pressionados, por um lado, pela responsabilização e avaliação de resultados e, por outro lado, pela falta de autonomia e condições propícias para uma gestão escolar democrática. Palavras-chave: Educação. Gestão democrática. Participação.